2012
DOI: 10.3109/10837450.2011.653816
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the degree of esterification on the release characteristics ofin situgelling pectin formulations for oral sustained delivery of paracetamol

Abstract: The aim of this study was to examine the effect of a change of the degree of esterification of pectin on the in situ gelation and release characteristics of 1.5% (w/v) pectin solutions over a wide pH range. Formulations of pectin with degrees of esterification of 9% (DE9) and 31% (DE31) containing complexed calcium ions formed gels in vitro at pH 1.2 as a consequence of cross-linking of the pectin chains by free calcium ions released from the complex. In vitro release of paracetamol from these gels was diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In this experiment, the histamine H 2 -receptor antagonist famotidine (15 mg/kg) was injected intraperitoneally in mice 30 min before oral administration of insulin and penetratin. 16) As shown in Fig. 6, we confirmed that the pH of the gastric fluid of mice receiving famotidine was neutralized and modified pH could be maintained for at least 30 min.…”
Section: Exploring Optimized Doses Of Insulin Based On Spr Analysis Asupporting
confidence: 62%
See 1 more Smart Citation
“…In this experiment, the histamine H 2 -receptor antagonist famotidine (15 mg/kg) was injected intraperitoneally in mice 30 min before oral administration of insulin and penetratin. 16) As shown in Fig. 6, we confirmed that the pH of the gastric fluid of mice receiving famotidine was neutralized and modified pH could be maintained for at least 30 min.…”
Section: Exploring Optimized Doses Of Insulin Based On Spr Analysis Asupporting
confidence: 62%
“…1B. 16) In a preliminary experiment, the pH of gastric fluid was checked using universal pH indicator paper (Macherey-Nagel GmbH & Co., KG, Düren, Germany) before and after the oral dosing of PBS or the intraperitoneal (i.p.) injection of famotidine.…”
mentioning
confidence: 99%
“…The potential applications of pectin with DE9 as a formulation with a degree of esterification (DE) of 9%, and DE31 as a formulation with a degree of esterification of 31%, were demonstrated as sustaining the floating of paracetamol with further in situ gelation in the stomach of gastric acidity-controlled rats with variety of pH (1.2–6.8) [128]. A substantial distinction regarding the in vivo gelling characteristics of the pectin DE9 and DE31 patterns was revealed by testing the stomach contents of gastric acidity-controlled rats at high pH intervals, following the oral administration of 1.5% ( w / v ) pectin sols.…”
Section: Pectin As Carriers For Drug Deliverymentioning
confidence: 99%
“…A substantial distinction regarding the in vivo gelling characteristics of the pectin DE9 and DE31 patterns was revealed by testing the stomach contents of gastric acidity-controlled rats at high pH intervals, following the oral administration of 1.5% ( w / v ) pectin sols. The significant gastric acidity influenced the decrease of the DE31 effectiveness, in comparison with compositions produced from pectin with DE9, and the stomach pH surged to 5.5 [128].…”
Section: Pectin As Carriers For Drug Deliverymentioning
confidence: 99%